Proportion of CD44+ subset of tumour cells in single cell suspension prepared from FFPET sections directly correlates with histological subtyping of head and neck squamous cell carcinoma - Kashif, Muhammad; Minhas, Sadia; Jahan, Shah; Samad, Afra; Shahzad, Faheem; Tahir, Romeeza; Nagi, Abdul Hanan; Afzal, Nadeem (Penerbit Universiti Kebangsaan Malaysia, 2023)
CD44 expression in tumours imparts potential to progress, metastasize, recurrence, and resistance against antineoplastic therapy. In this study, we sought to describe the variation in the immuno-expression and numeration of MDR1+ and CD44+ potential cancer stem cells in different histological grades and subtypes of head and neck squamous cell carcinoma (HNSCC). Flow-cytometric analysis was performed on single cell suspension prepared from formalin fixed paraffin embedded tissue (FFPET) sections of HNSCC using anti-CD44 and anti-MDR1/ABCB-1 primary monoclonal antibodies. Immunohistochemical (IHC) staining was also carried out using both of these antibodies on HNSCC tissue sections mounted on super frosted glass slides. On immunohistochemical analysis, the mean IRS for CD44 and MDR1 were 8.6364 ±3.02114 and 1.5909 ±1.27674 respectively. When mean immune-expression scores of CD44 antibody and MDR1/ABCB-1 were compared with histological grades and subtypes of HNSCC, the relationship was found to be statistically insignificant. Interestingly, a strong statistical difference (p = 0.000) was observed when the mean score of subset of dysplastic squamous epithelial cells with characteristics of cell stemness (CD326+CD44+) was compared among different histological subtypes of HNSCC using flowcytometric analysis. While no statistically significant association was observed when the mean score for subset of dysplastic cells with potential of drug resistance (CD44+MDR1+) was compared among different histological subtypes of HNSCC. Although potential cancer stem cell marker CD44 and the multidrug resistance maker MDR1/ABCB co-expressed in HNSCC but the proportion of CD326+CD44+ subset of tumour cells (potential cancer stem cells/CSCs) significantly correlates with least aggressive to more aggressive tumour subtypes.